2008
DOI: 10.1001/archneur.65.11.1434
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Beta–Induced Restoration of Regulatory T-Cell Function in Multiple Sclerosis Is Prompted by an Increase in Newly Generated Naive Regulatory T Cells

Abstract: Background: Naturally occurring regulatory T (T reg ) cells are functionally impaired in patients with relapsingremitting multiple sclerosis. We recently showed that prevalences of newly generated CD31-coexpressing naive T reg cells (recent thymic emigrant-T reg cells) are critical for suppressive function of circulating T reg cells, and a shift in the homeostatic composition of T reg -cell subsets related to a reduced de novo generation of recent thymic emigrant-T reg cells may contribute to the multiple scle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 30 publications
3
45
2
1
Order By: Relevance
“…However, interferon-β has previously been demonstrated to affect the T regulatory cell compartment [33] and was reported to induce BDNF secretion in immune cells [34,35]. Therefore, we cannot exclude that pleiotropic ‘beneficial’ interferon effects overlay the potential immunological effects of physical activity.…”
Section: Discussionmentioning
confidence: 96%
“…However, interferon-β has previously been demonstrated to affect the T regulatory cell compartment [33] and was reported to induce BDNF secretion in immune cells [34,35]. Therefore, we cannot exclude that pleiotropic ‘beneficial’ interferon effects overlay the potential immunological effects of physical activity.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the fact that IFN-b therapy acts at various levels within the putative pathogenesis of MS (36), the examples how IFN-b therapy reconstitutes tolerogenic factors of the immune systems are of specific importance (e.g., recovery of FoxP3 Treg function) (37) and upregulation of tolerogenic molecules on APC (e.g., B7H1 on monocytes) (38). It has been shown that pDCs show an impaired maturation in response to IFN-b (13), which among other markers is reflected by a lower MHC class II expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CD25, CD127 , and CD58 , all of which contribute to Treg function, have been identified as risk alleles for susceptibility to MS, further suggesting an intrinsic Treg defect [8487]. Treating MS patients with IFN-β appears to restore suppressive function to Tregs [83, 88, 89]. Thus, the discovery that enhanced Treg activity can ameliorate EAE, as well as studies of Treg activity using reporter mice, have provided insight into current therapies and led to new therapeutic strategies for targeting pathways that enhance Treg function.…”
Section: Modeling Immune-mediated Mechanisms In Eaementioning
confidence: 99%